Gelam Honey Inhibition of Bacterial Pathogen: Determination of MIC and NIC Values Using the Lambert-Pearson Model (Asian Journal of Plant Biology, 2022)
The curative effect of honey is due to the fact that it possesses antibacterial activity, it keeps wounds moist by retaining their natural moisture, and the honey's high viscosity contributes to the formation of a protective barrier that helps to keep infections at bay. All of these properties work together to make honey an effective wound healer. In addition, the immunomodulatory action that it possesses plays a part in the process of wounds healing. Honey's antibacterial efficacy against bacterial pathogens is frequently indicated by the lowest minimum inhibitory concentration (MIC) and the non-inhibitory concentration (NIC) values. The reality that all of the MIC and NIC techniques that are now being used are just semi-quantitative in nature is the primary issue that develops as a consequence of this circumstance. Use of data-driven nonlinear regression analysis as one of the ways to determine this value is one of the methods that has the highest degree of precision out of all of the methods that may be used. Using the Lambert-Pearson modified Gompertz model, it was feasible to successfully determine the MIC and NIC of the gelam honey against different bacterial pathogen remodels. According to the Shukor's chart for MIC values, S. aureus  is the pathogen most sensitive to gelam honey followed by E. coli and P. aeruginosa while the MIC value for B. cereus overlaps with P. aeruginosa indicating that more research is required to determine where B. cereus falls in terms of sensitivity. There is a good match between the data and the Lambert-Pearson model, with values for the coefficient of determination (R2) ranging from 0.94 to 0.97. Based on these findings, it appears that honey from gelam trees has the potential to inhibit the formation of bacterial infections.
Keywords: Gelam honey; Antibacterial; MIC; NIC; Lambert-Pearson model